2009
DOI: 10.1634/theoncologist.2008-0214
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Monoclonal Antibodies: New Therapeutic Agents in Non-Hodgkin’s Lymphomas

Abstract: 1. Utilize new therapeutic agents with proven efficacy in the chemotherapy-and monoclonal antibody-refractory NHL setting.2. Analyze the study of these new agents in lymphoma subtypes and in relation to genetic aberrations of the lymphoma.3. Differentiate the toxicity of these new agents from that of chemotherapy.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTThe availability of active monoclonal antibodies, either as single agents or in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 128 publications
(128 reference statements)
0
2
0
1
Order By: Relevance
“…Гиперэкспрессия HDACs наблюдается при многих опухолевых заболеваниях, в том числе и при ГМ. В настоящее время синтезированы ингибиторы HDACs, которые используются в терапии ТКЛК, проводятся исследования для создания новых, более эффективных форм ингибиторов HDACs [69].…”
Section: эпигенетические механизмы патогенеза гмunclassified
“…Гиперэкспрессия HDACs наблюдается при многих опухолевых заболеваниях, в том числе и при ГМ. В настоящее время синтезированы ингибиторы HDACs, которые используются в терапии ТКЛК, проводятся исследования для создания новых, более эффективных форм ингибиторов HDACs [69].…”
Section: эпигенетические механизмы патогенеза гмunclassified
“…Mantle cell lymphoma (MCL) represents a subgroup of poor prognostic, high-risk NHL with an aggressive biology and short progression-free as well as overall survival (1-3). Therefore, identification and evaluation of active new agents and new drug combinations against MCL (4-8), including exploratory single agent Phase II clinical studies in relapsed or refractory MCL (4,9-16), as well as more intense multimodality strategies with immunochemotherapy and hematopoietic stem cell transplantation for eligible patients (17,18), have been focal points in translational lymphoma research (3). Likewise, several research teams have embarked upon molecular target discovery efforts to identify new druggable targets in MCL cells using integrated multi-platform laboratory and in silico research tools (19-22).…”
Section: Introductionmentioning
confidence: 99%
“…[175][176][177][178] SYK is a new target for the management of B-lineage leukemias and lymphomas, 179 as it regulates apoptosis by controlling activation of the phosphoinositide 3-kinase/AKT, nuclear factor-kappa B, and signal transducer and activator of transcription 3 pathways, which are all very important in the signaling of the stem cell lineage. 180,181 Cely et al 182 reported a different approach by developing a nanotechnology-based platform that can be used to target a very selective SYK inhibitor for the lymphoma cell.…”
mentioning
confidence: 99%